Introduction: Banishing Women: The Law and Politics of Abortion Travel - Kelly, Lisa; Tuszynski, Nicole (Columbia Journal of Gender and Law, 2016)
In her Introduction to the inaugural issue of the Columbia Journal of and Law(JGL), Ruth Bader Ginsburg traced the gendered history of Columbia Law School from 1928, when the first female student was admitted, to 1990, when women composed nearly half the student body. Reflecting on this change, she asked, “Does women’s participation affect the way law business is conducted, and the shape and direction of legal development?” In pursuing this “large question,” Justice Ginsburg contemplated a feminist movement that would offer “a spacious home” for “all who have the imagination and determination to work for the full realization of human potential.”